Radiographic Analysis of Complications Following Composite Restoration of Posterior Crown Defects - Mykyievych Назарій; Makeyev Валентин (Actual Dentistry, 2026)
Background. Composite restorations of posterior teeth are widely used in clinical dentistry; however, despite the application of modern materials and adhesive systems, the incidence of complications remains high. This is particularly relevant for proximal surfaces of molars and premolars, where anatomical features complicate the formation of proper marginal adaptation and proximal contact, thus justifying radiographic evaluation as an objective method for assessing restoration quality. Objective. To analyze radiographically detected complications following the restoration of coronal defects of posterior teeth with composite materials and to determine their frequency depending on tooth localization and morphology. Materials and Methods. A total of 183 periapical radiographs of maxillary and mandibular molars and premolars restored with composite materials due to moderate and deep carious lesions involving proximal surfaces were analyzed. Marginal adaptation defects, proximal contact loss, secondary caries, and their combinations were assessed, taking into account the localization of defects (MO, OD, MOD). Results. The most frequent radiographically detected complications were marginal adaptation defects (34.5%) and loss of proximal contact (26.3%). Isolated secondary caries was observed in 4.8% of cases; however, when combined with an overhanging restoration margin or proximal contact loss, its prevalence increased to 34.4%. The highest number of complications was recorded in mandibular molars (38.8%), which may be related to their anatomical characteristics and limited accessibility for visual inspection. Conclusions. Radiographic analysis enabled the detection of errors and complications not evident during clinical examination, particularly the absence of proximal contact and overhanging restoration margins, which are iatrogenic in nature and may lead to further pathological changes in hard dental tissues. These findings highlight the need to improve and refine restorative techniques aimed at reducing the frequency of such complications and enhancing the long-term clinical effectiveness of composite restorations.